2015
DOI: 10.5194/cp-11-1751-2015
|View full text |Cite
|
Sign up to set email alerts
|

Did high Neo-Tethys subduction rates contribute to early Cenozoic warming?

Abstract: Abstract. The 58-51 Ma interval was characterized by a long-term increase of global temperatures (+4 to +6 • C) up to the Early Eocene Climate Optimum (EECO, 52.9-50.7 Ma), the warmest interval of the Cenozoic. It was recently suggested that sustained high atmospheric pCO 2 , controlling warm early Cenozoic climate, may have been released during Neo-Tethys closure through the subduction of large amounts of pelagic carbonates and their recycling as CO 2 at arc volcanoes. To analyze the impact of NeoTethys closu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 101 publications
(197 reference statements)
0
10
0
Order By: Relevance
“…Similarly, Kerrick and Caldeira () suggested that carbon degassing due to metamorphism of Indian margin rocks along the Himalayan belt enhanced paleoatmospheric carbon levels, although revised estimates point to a minor contribution to early Eocene warming (Kerrick & Caldeira, ). A reduction of carbon dioxide emissions is inferred between ~50 and 40 Ma, synchronous with the observed phase of climate cooling, when Tibetan arc volcanism was waning after collision between India and Eurasia (Hoareau et al, ; Jagoutz et al, ; Figure ).…”
Section: Solid Earth Control On Cenozoic Climate Coolingmentioning
confidence: 89%
See 2 more Smart Citations
“…Similarly, Kerrick and Caldeira () suggested that carbon degassing due to metamorphism of Indian margin rocks along the Himalayan belt enhanced paleoatmospheric carbon levels, although revised estimates point to a minor contribution to early Eocene warming (Kerrick & Caldeira, ). A reduction of carbon dioxide emissions is inferred between ~50 and 40 Ma, synchronous with the observed phase of climate cooling, when Tibetan arc volcanism was waning after collision between India and Eurasia (Hoareau et al, ; Jagoutz et al, ; Figure ).…”
Section: Solid Earth Control On Cenozoic Climate Coolingmentioning
confidence: 89%
“…The short‐lived magmatic flare‐up is in striking coincidence with the Early‐Eocene Climate Optimum, suggesting a cause‐effect relationship between the magmatic and climatic event, a possibility that was only marginally investigated thus far. Subduction of the carbonate‐rich Indian passive margin succession in the middle Paleocene may have enhanced carbon recycling at the Transhimalayan volcanic arc (e.g., Kent & Muttoni, ; van Hinsbergen et al, ; Hoareau et al, ). Hoareau et al () modeled the volume of subducted materials and the amount of CO 2 emitted along the northern Tethyan margin and the effects of estimated CO 2 fluxes on global climate.…”
Section: Solid Earth Control On Cenozoic Climate Coolingmentioning
confidence: 99%
See 1 more Smart Citation
“…If arc volcanoes, associated with subduction zones, provide a quick return of materials to the surface, the direct melting of oceanic crust may increase the amount of fluid released, suggesting a recycling of suducted carbon higher than today. According to this assumption, the decarbonation efficiency may exceed Cenozoic values used as reference [Hoareau et al, 2015]. We thus explored the effect of the recycling (R) using the Cenozoic value as reference (R=0.1, corresponding to a recycling efficiency of 10%) and values 3 times higher (R=0.3, a recycling efficiency of 30%).…”
Section: Model Set-up and Boundary Conditionsmentioning
confidence: 99%
“…The India plate drifted at a high velocity with the simultaneous counterclockwise rotation until its collision with Eurasia in the Paleocene-Eocene. Although the timing of collisions of Africa-Arabia and India with Eurasia is slightly different, both Africa-Arabia and India plates show consistent counterclockwise rotation with the same angular velocity (Hoareau et al, 2015). The whole process can be concluded as that both the Africa-Arabia and India plates rotated counterclockwise around the Euler pole of northwest Africa, which led to the final closure of the Neo-Tethys Ocean.…”
Section: Plate Rotation In Non-free Boundary Conditions Controls Evol...mentioning
confidence: 91%